PENGARUH LITERASI KEUANGAN TERHADAP KESEJAHTERAAN KEUANGAN KELUARGA DENGAN ANAK PENYANDANG DISABILITAS: PERAN PERILAKU KEUANGAN SEBAGAI VARIABEL MEDIASI (Studi Kasus Pada Komunitas FKD Sinar Sejahtera Klojen Kota Malang): (Studi Kasus Pada Komunitas FKD Sinar Sejahtera Klojen Kota Malang) - Fatmawati Sholichah; Aditya Rusli; Sudarjo; Sukrispiyanto; M. Nasikh (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2026)
Families with children with disabilities face more complex economic challenges than families in general due to ongoing special needs, such as the costs of therapy, health services, education, and mentoring. This condition requires good financial management skills to achieve family financial well-being. This study aims to analyze the effect of financial literacy on the financial well-being of families with children with disabilities, with financial behavior as a mediating variable. The study applied a quantitative approach through a survey method to 50 parents or guardians of children with disabilities who are members of the Sinar Sejahtera Disability Family Forum (FKD) in Klojen District, Malang City. Data were obtained by questionnaire and analyzed using PLS-SEM (Partial Least Squares Structural Equation Modeling). These findings show that financial literacy has a positive and significant impact on financial behavior (β = 0.984; t = 18.435) and family financial well-being (β = 0.455; t = 2.940). However, financial behavior did not significantly impact family financial well-being (β = 0.130; t = 0.884), thus failing to mediate the relationship between financial literacy and financial well-being. These findings suggest that financial literacy is a key factor contributing to improved financial well-being in families with children with disabilities. This research has implications for developing more targeted financial education and economic empowerment programs to improve the well-being of families with disabilities. Keywords: financial literacy, financial behavior, financial well-being, families with disabilities, PLS-SEM.